EFFECTS OF A DEVELOPED FLIPPED CLASSROOM PACKAGE ON NCE STUDENTS' ACADEMIC PERFORMANCE IN EDUCATIONAL TECHNOLOGY CONCEPTS IN SOUTHWEST, NIGERIA - Sade, GANIYU; Kunle, OLASEDIDUN (African Journal of Education and Practice, 2022)
Purpose: This study was carried out in Colleges of Education in South-west, Nigeria to investigate the effects of a developed flipped classroom package on academic performance of NCE students in selected concepts of Educational Technology. Methodology: The study adopted 2 x 2 x 3 factorial matrix quasi-experimental design of pre-test, post-test, non-randomized, non-equivalent control group type. Two hypotheses were raised and tested for the study. Data were analysed using inferential statistics. A sample of three hundred and sixty respondents drawn from twelve government owned colleges of education in south-west, Nigeria participated in the study. The research instruments used were grouped into two, namely, Treatment Instrument (TRI) and Test Instrument (TEI) on Educational Technology. The treatment instrument was the flipped classroom package designed to deliver instruction to students in the experimental group. The Test Instrument was used to determine both pre-test and post-test performance of both groups. Instrument reliability was tested using Cronbach Alpha formula and reliability co-efficient of 0.89 was gotten. Findings: Findings from the study revealed that NCE students performed better when taught using flipped classroom package compared with their counterparts taught with conventional method of teaching and that NCE female students performed better than their male counterparts when taught using flipped classroom package in Educational Technology concepts. Unique contribution to theory, practice and policy: It was, therefore, recommended among others that Educational Technologists should expose NCE students to ICT-Based instructional strategies like Flipped classroom to promote students' autonomy to knowledge acquisition, discovery learning and student-centered instructional approach. Educational Technologists should endeavour to develop and utilize FC for teaching Educational Technology Concepts. This will further increase teachers' knowledge on new innovations in ICT-Based instructional strategies. Teacher trainers should endeavour and be encouraged to use flipped classroom as an instructional delivery method for the improvement of instructional quality that would enhance students' centred learning theory which would promote learning styles, peer assisted, collaborative learning, cooperative learning and problem based learning that will bring about active learning for overall development of the learners. The regulatory agency for colleges of education (National Commission for Colleges of Education) should mandate the management of colleges of education to take cognizance of importance of flipped classroom and put it into use. This study was premised on the students' centred learning theory identified above. This implies that the students' centred learning theory could be applied to similar studies in the future.